Site-directed mutagenesis in the DNA linking site of bacteriophage phi 29 terminal protein: isolation and characterization of a Ser232----Thr mutant. - Garmendia, C (1988)
By site-directed mutagenesis we have changed the serine residue 232 of the phi 29 terminal protein, involved in the covalent linkage to dAMP for the initiation of replication, into a threonine residue. The mutant terminal protein has been purified to homogeneity and shown to be inactive in the formation of the initiation complex; nevertheless, the mutant protein retains its ability to interact with the phi 29 DNA polymerase and with the DNA. The results obtained indicate a high specificity in the linking site of the terminal protein.